Royal Jelly and Human Health: A Systematic Literature Review - Rudi Ruhdiat (Jurnal Ragam Pengabdian, 2026)
Royal jelly is a natural bioactive substance produced by Apis mellifera worker bees and has attracted increasing scientific attention due to its potential health benefits. Rich in proteins, fatty acids, vitamins, and unique compounds such as 10-hydroxy-2-decenoic acid (10-HDA), royal jelly has been widely investigated for its biological and therapeutic properties. This study aimed to systematically review the scientific evidence regarding the effects of royal jelly on human health. A systematic literature review was conducted following PRISMA guidelines using databases including PubMed, Scopus, Web of Science, Cochrane Library, and Google Scholar for studies published between 2010 and 2025. Eligible studies included randomized controlled trials, meta-analyses, cohort studies, and relevant preclinical research. From 150 identified records, 20 studies met the inclusion criteria and were included in the final synthesis. The findings indicate that royal jelly demonstrates multiple potential health benefits, including improved glycemic control, better lipid metabolism, enhanced immune response, anti- inflammatory effects, improved skin health, reproductive benefits, and possible anticancer activity. Overall, royal jelly shows promise as a nutraceutical agent that may support metabolic, cardiovascular, and immune health, although further standardized clinical trials are required to confirm optimal dosage and long-term safety